(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article examines the role of foreign investment in the economic development of Uzbekistan, highlighting recent reforms and challenges faced by foreign investors. It delves into the efficiency and sustainability of foreign investment projects and explores strategies for improving the investment climate. Using a mixed-methods research approach, the study identifies key factors affecting the success of foreign investments, including regulatory frameworks, infrastructure, and political stability. Recommendations are provided to address these challenges, ensuring Uzbekistan attracts more investments, fosters economic growth, and facilitates the transfer of technology. The findings offer valuable insights for policymakers and practitioners in Uzbekistan and other developing countries aiming to enhance their foreign investment strategies.